Influence of soil compaction on the development of soybeans - Nogueira, Sandra dos Santos Sevá; Manfredini, Sidneide (Pesquisa Agropecuaria Brasileira, 2014)
An attempt was made to simulate the mechanical soil layer compaction that may develop in clay soils and to study its effect on the soybean (Glycine max (L.) Merrill) growth. The experiment was carried out in cylindrical pots filled with clay soil in such a way that the medium third was prepared at three density values (1.22, 1.44 and 1.75 g/cm ), keeping she top and bottom layers the original density (0.90 g/cm3). Soybean plants of Santa Rosa cultivar were analyzed as to dry weight of roots, leaves, stems and pods, as well as length of stem, and number of internodes. Compaction of the middle layer at the density of 1.75 g/cm3 hindered root passage and induced a greater root development in the upper parts of the plants induced by the treatments. In this experiment, compaction had no effect on the soybean yield, most likely due to sufficiency of water and nutrients in the soil.